Optimization design of porthole die and study on microstructures and mechanical properties for an Al–Li alloy hollow profile - Yuelin Wang; Guoqun Zhao; Junquan Yu; Xiaowei Wang; Shaoqiang Xu (Journal of Materials Research and Technology, 2024)
In this paper, a hollow Al–Li alloy profile was taken as an example, and the optimization design method of Al–Li alloy porthole die was given. Compared with the basic die design, the optimized die reduces the standard deviations of velocity and temperature as well as the maximum equivalent stress, resulting in a significant reduction of the distortion degree of the extruded profile, and the optimized die meets the strength requirements. The microstructures, mechanical properties and strain distributions of the longitudinal welds and matrices of the extruded profile were analyzed. It is found that the longitudinal welds are well welded without macro/micro defects. The fracture of tensile specimens all occurred at the matrices instead of welds, and the mechanical properties in the thick-walled matrices are much lower than those in the thin-walled matrices. The grain size in the thick-wall matrices is much coarser and more ununiform than that in the thin-walled matrices, which is caused by the low strain in the thick-walled matrices. For increasing the strain amount and uniformity of local zone of the extruded profile, an innovative method through adding baffle-blocks in the portholes was proposed.